FRI0623-HPR Kinesiophobia Affects Range of Knee Flexion at Early Stage Following Anterior Cruciate Ligament Reconstruction. (15th July 2016) - Demirbüken, I.; Özgül, B.; Arıkan, E.; Tonga, E.; Polat, M.G.
Abstract : Background: One of the most common complications following anterior cruciate ligament (ACL) reconstruction in sport rehabilitation is loss of knee motion (1). A fear of re-injury of ACL may contribute limitations of knee functions in terms of range of motions during rehabilitation process (2). Some athletes are not able to return to their pre-injury level due to loss of knee function and fear of motion in other words kinesiophobia. Objectives: To investigate the relationship between range of motion (ROM) of the knee which is an important target in rehabilitation and kinesiophobia degree following ACL reconstruction in professional athletes. Methods: The study was carried out with 14 certified athletes (8 male and 6 female, mean age: 21.5±5.86 years; mean body weight: 68.7±15.2 kg; mean height: 177.5±10.3 cm) who had unilateral ACL reconstruction and started post-op physiotherapy treatment participated in the study. All assessments were performed at 15th day following reconstruction. Kinesiophobia degrees of the athletes were assessed with Tampa Kinesiophobia Scale. A high score obtained from the scale indicates a high degree of kinesiophobia. Active and passive flexion degrees of knee joint were measured by using goniometer in accordance with Kendall-McCreary's criteria. All ROM measurements were performed 3 times and mean values of 3 measurements were saved for data analysis. The relationships between kinesiophobia degrees and active & passive flexion of the knee joint were analyzed by using Spearman's Correlation test. Results: There was a strong negative relationship between the kinesiophobia degrees and active (r=-0.881, p<0.001) & passive (r=-0.887, p<0.001) ROM degrees of knee flexion. Conclusions: One of the important aims of the treatment following ACL reconstruction is regaining functional level before injury and providing an early return to sports without any movement limitation. The results of this study revealed that presence of kinesiophobia at early stage influenced active and passive range of motion of knee joint negatively. Assessment of the kinesiophobia at early stage in ACL reconstructions could make a significant contribution to rehabilitation process in terms of achieving projected ranges of motions sooner in clinical settings. References: Peter J. Millett, MD, MSc. Sports Medicine and Orthopaedic Surgery. ACL Reconstruction Rehabilitation Protocol. [Accessed 2016 January 30] Available from: http://drmillett.com/wp-content/uploads/2014/03/acl-rehab-protocol.pdf Kvist, J., Ek, A., Sporrstedt, K., & Good, L. (2005). Fear of re-injury: a hindrance for returning to sports after anterior cruciate ligament reconstruction. Knee surgery, sports traumatology, arthroscopy, 13(5), 393–397. Disclosure of Interest: None declared